The Ratings Game: Asymmetry in Classification - Waguespack, David M.; Sorenson, Olav (Organization Science, 2011)
Categorization processes are generally treated as consistent mappings of the underlying characteristics that they group. Yet, in many cases, the identities of actors influence these processes. When identity matters, high-status actors often obtain more favorable classifications. We examine these processes in the context of the Motion Picture Association of America's parental guidance classifications of movies (G, PG, R, NC-17). We find that, conditional on a given level of content, films distributed by the Association's members and those that involve more central producers and directors receive more lenient classifications than those carried by independent distributors and involving more peripheral personnel. Conversely, and again conditional on content, films involving directors with a history of producing R-rated features receive more restrictive ratings. We discuss the mechanisms that might account for these effects. Regardless of the mechanism, however, because ratings influence revenue and consequently profitability, the movie certification system in the United States places independent distributors and peripheral individuals at a disadvantage, relative to their larger and more central rivals.